Cell cycle regulation in NAFLD: when imbalanced metabolism limits cell division - Caldez, Matias J. (Hepatol Int, 2020)
Cell division is essential for organismal growth and tissue homeostasis. It is exceptionally significant in tissues chronically exposed to intrinsic and external damage, like the liver. After decades of studying the regulation of cell cycle by extracellular signals, there are still gaps in our knowledge on how these two interact with metabolic pathways in vivo. Studying the cross-talk of these pathways has direct clinical implications as defects in cell division, signaling pathways, and metabolic homeostasis are frequently observed in liver diseases. In this review, we will focus on recent reports which describe various functions of cell cycle regulators in hepatic homeostasis. We will describe the interplay between the cell cycle and metabolism during liver regeneration after acute and chronic damage. We will focus our attention on non-alcoholic fatty liver disease, especially non-alcoholic steatohepatitis. The global incidence of non-alcoholic fatty liver disease is increasing exponentially. Therefore, understanding the interplay between cell cycle regulators and metabolism may lead to the discovery of novel therapeutic targets amenable to intervention.